2016
DOI: 10.1186/s12935-016-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TP53 and CDH1 genes in hepatocellular cancer spheroid formation and culture: a model system to understand cancer cell growth mechanics

Abstract: BackgroundSpheroid based culture methods are gaining prominence to elucidate the role of the microenvironment in liver carcinogenesis. Additionally, the phenomenon of epithelial-mesenchymal transition also plays an important role in determining the metastatic potential of liver cancer. Tumor spheroids are thus important models to understand the basic biology of liver cancer.MethodsWe cultured, characterized and examined the formation of compact 3-D micro-tumor spheroids in five hepatocellular carcinoma (HCC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 80 Recent studies have shown that as a key transcription factor of CDH1 that participates in the formation of MSC spheroids, 67 , 81 the TP53 status is crucial in determining the morphology and size of the spheroidal structures. 82 Hence, when DPSCs form aggregates under low-attachment conditions through enhanced cadherin binding induced by TP53, TP53 may simultaneously increase the expression of miR-1246, leading to its increased level in exosomes. Another suggested mechanism acts on the epigenetic level.…”
Section: Discussionmentioning
confidence: 99%
“… 80 Recent studies have shown that as a key transcription factor of CDH1 that participates in the formation of MSC spheroids, 67 , 81 the TP53 status is crucial in determining the morphology and size of the spheroidal structures. 82 Hence, when DPSCs form aggregates under low-attachment conditions through enhanced cadherin binding induced by TP53, TP53 may simultaneously increase the expression of miR-1246, leading to its increased level in exosomes. Another suggested mechanism acts on the epigenetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Differential E-cadherin expression levels have been associated with altered spheroid formation in head and neck carcinoma cell lines 15 . Differential E-cadherin expression was also associated with compact spheroid formation in hepatocellular carcinoma cell lines 16 , 17 and in renal cell carcinoma 18 . In addition spheroid models were used to identify cooperative roles for E-cadherin and the desmosome proteins DSG2 and DSC2 in colon and breast carcinoma cell lines 19 .…”
Section: Introductionmentioning
confidence: 90%
“…One SNP array analysis of 125 HCC patients revealed that 20.8% of TP53 mutations were inactivating mutations 52. Recently, it was found that TP53 mutant cell lines showed a smaller cell size in a hepatocellular cancer spheroid formation test, which resulted from the lower CDH1 expression levels 53. Moreover, evidence demonstrated the mutant-p53 could affect the expression of Twist1 and Smad interacting protein 1 (SIP1) and further regulate E-cadherin in adrenocortical carcinoma 54.…”
Section: Gene Mutationsmentioning
confidence: 99%